Gestão de cartas precatórias: uma proposta de aperfeiçoamento para a prestação jurisdicional - Costa, Igor Rodrigues da (Universidade Federal do Tocantins, 2019)
It is a propositional dissertation that aimed to improve the system of management of precatory letters, in order to guarantee better efficiency to the jurisdictional provision by precatory letters. Initially, the nine articles that comprise the communication of a procedural act of the species "letter" in the Code of Civil Process, articles 260 to 268, are showed, with the scope of delimiting the theme. The species of letter: precatory, order, rogatory and arbitration are analyzed in detail according to the process doctrine constituting theoretical reference. The field dimension of the survey notes that from September 1999, the date of creation of the specialized Gurupi Precatory Law Court, up to December 2018, 30.151 precatory letters were received and the situation of the processes month to month during this period; to provide speed and efficiency in the fulfillment of the letters, given that the annual average amount of receiving 2200 letters is considered as a challenge, as well as the management in the Judiciary is fundamental for the improvement of the jurisdictional provision. With the quantitative and qualitative analysis of the precatory letters, it can be seen that failure to comply with the requirements of the Code of Civil Process combined with non-compliance with the rules of the Tocantins State Courts of Justice, constitute the factor of effective non-compliance with letters, and the absence of essential documents, which should necessarily accompany the letter and the insufficiency and/or lack of addresses declined in the letters are the problems with the highest incidence rate. To communicate by letter of precatory is necessary and precise, because not all process is satisfied in the own region, for that reason must be observed all the legal norms. The research concluded by requesting the Tocantins State Courts of Justice to forward recommendations to all the courts that are part of the Court of Justice of Tocantins (TJTO), as well as to the Corregedoria of the other States and Corregedoria of the National Council of Justice. (CNJ) to comply with the requirements of article 260 and sequences of the CPC when issuing pre-emptive letters and the drafting of a single standard model of letter of formal notice that establishes the identity of the TJTO and meets all the requirements of the CPC.